TEACHING ENGLISH DURING THE PANDEMIC: BIBLIOMETRIC ANALYSIS - Isti'anah, Arina; Wijanarka, Hirmawan (LLT Journal: A Journal on Language and Language Teaching, 2023)
The COVID-19 pandemic has led to massive publications indexed in various databases, which provide platforms for research communities, including teachers and researchers, to disseminate their experiences during the pandemic. This paper employed bibliometric analysis to investigate the keywords “teaching English in the pandemic” in the Scopus database to determine how the research is produced. This research used Vos Viewer to analyze the co-authorship and co-occurrences of the keywords from the bibliographic information downloaded from the Scopus database by limiting its search to 2020-2022 under the scope of social sciences and humanities. From the 444 documents eligible for the review, this paper indicates two main points: (1) the co-authorship of research publication has been equally distributed and produced through collaboration despite ample opportunities for joint research among organizations, and (2) the co-occurrences of the keywords show three major research trends during the COVID-19 pandemic: pedagogical best practices, pedagogical experience, and pedagogical strategies. This paper exemplifies how knowledge and publications are generated within a certain field, enabling the research community to foster collaboration and produce articles that incorporate pertinent keywords currently under discussion.